THE ENDEAVOUR OF LANGUAGE MAINTENANCE (A CASE STUDY EXPERIENCED BY AN INDONESIAN IMIGRANT IN NORWAY) - Fathimah Nuruz Zakiyah; Hero Gunawan (English Journal Literacy Utama, 2020)
This research discusses language maintenance experienced by an Indonesian immigrant in Norway. The method used in this research is descriptive qualitative method by using two instruments: interview and questionnaire. Two types of questions are used in the instrument, i.e. close-ended and open-ended ones. The objective of this research is to explain what kinds of activities as the endeavor of the immigrant in maintaining his native language (Indonesian). The result indicates that the activities conducted by the immigrant as the effort to maintain his native language (Indonesian) cover: 1) Joining the community of Indonesian immigrant in which he can do many activities like gathering together, having meals and travelling together, and discussing various topics including religious ones, 2) periodically-homecoming through which he can visit his family, relatives and friends such as during the Idul Fitri Holiday, 3) communicating with the family (once a week) in Indonesia through telephone or any other media like skype (video call) and facetime, even almost every day if using messaging app infacebook messenger, 4) listening to Indonesian songs, 5) watching Indonesian films, 6) looking for Indonesian news, 7) utilizing social media such as Facebook, Twitter, Instagram, Path and Snapchat as communication media with his friends in Indonesia.